DYSTOCIA DUE TO FETAL CONGENITAL GOITER IN NON-DESCRIPT DOE: A CASE REPORT - Sasidharan, Jisna Kuttiyeri; Gupta, Shashikant; Pradeep; Jackson, Amala; Chandra, Pradeep; Kumar, Brijesh; Ghosh, ubrata Kumar; Khan , Meraj Haider (The Indian Journal of Animal Reproduction, 2023)
A nondescript doe, in its first pregnancy, presented with history of complete gestation, straining, and brownish-red discharge from the vagina for the past five days. Upon conducting a thorough gynecological examination, it was discovered that the doe had a fetus lodged in the birth canal in a breech presentation. Manually corrected the position of the fetus and gently pulled it out, ensuring proper lubrication of the birth canal. Two dead fetuses with congenital goiter were successfully delivered. The doe received appropriate treatment and made a smooth recovery without any complications.